Chemical Weapons in the Iran-Iraq War (1980-1988) Iraq Preparing for Chemical War - M. V. Supotnitskiy; N. I. Shilo; V. A. Kovtun (Вестник войск РХБ защиты, 2023)
The Iraqis became the first nation to use chemical weapons on the modern battlefield during the IranIraq War (1980-1988). There are no general reviews and research available on this issue in Russian. It also puts the Russian researchers in an unequal position in comparison with their Western and Middle Eastern colleagues, who have such information from a wide range of sources. This lack of knowledge limits our ability to understand the secret mechanisms that trigger modern chemical wars in the Middle East. The analysis in the present study is based on different Western sources, UN and CIA materials. The article shows that Iraq – a third world country with the population of 16,3 million people in 1980-ies and relatively low educational level – could start its chemical weapons program only due to the Western aid and assistance (supplies of the precursors, technologies and technical documentation, education of specialists, diplomatic support ect). Only due to this assistance the Iraqi`s chemical weapons program could become successful. The industrial production of chemical agents and chemical munitions of various tactical purposes was established by the Iraqis in less than 10 years. By the end of the 1980-ies, the Iraqi chemists laid the foundations of the future research in the sphere of toxic chemicals. The industrial base for the production of CW have also been established. For Russia, the success of the Iraq`s chemical weapons program is a warning. It means that technically backward, but oil rich quasi-state can acquire chemical weapons in a few years with the clandestine support of the same «sponsors», and use it both for provocations and for conducting combat operations in the regions, vital for Russia`s interests.